2018
DOI: 10.1016/j.vprsr.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the distribution of Rhipicephalus microplus and R. decoloratus in Zimbabwe

Abstract: Species distribution modelling is a very useful tool in vector management. Ticks are vectors of various pathogens which cause serious problems in livestock production in tropical countries. They have a high dispersal potential which is mainly facilitated by the movement of animals from one area to another. In light of the observed geographic expansion of Rhipicephalus microplus in Zimbabwe, we used species distribution modelling techniques to identify areas which may provide suitable habitats for the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
(31 reference statements)
1
16
0
Order By: Relevance
“…This elevation range corresponds to the humid subtropical zone (600-1200 masl) in Bhutan, characterized by an annual mean temperature of 19.5 • C and an annual rainfall of 1200-2500 mm [1]. This agrees with a study from Zimbabwe, where elevation was found as the most influential factor for the geographic distribution of R. microplus and R. decoloratus [54]. In Bhutan, areas with higher elevation are characterized by colder temperatures and low rainfalls, and that might result in such areas to be less suitable habitats for R. microplus.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This elevation range corresponds to the humid subtropical zone (600-1200 masl) in Bhutan, characterized by an annual mean temperature of 19.5 • C and an annual rainfall of 1200-2500 mm [1]. This agrees with a study from Zimbabwe, where elevation was found as the most influential factor for the geographic distribution of R. microplus and R. decoloratus [54]. In Bhutan, areas with higher elevation are characterized by colder temperatures and low rainfalls, and that might result in such areas to be less suitable habitats for R. microplus.…”
Section: Discussionsupporting
confidence: 86%
“…Rhipicephalus microplus was found more frequently in animals sampled in Pema Gatshel (98.2%) compared with those sampled in Trashigang (78.3%). Generally, this one-host tick species prefers warm and humid conditions [52], and temperature and rainfall are the most important climatic factors driving its geographic distribution [53,54]. Pema Gatshel, located at the warmer south, has the majority of its area dominated by subtropical climate with higher temperatures, abundant rainfall, and high relative humidity, while Trashigang is mainly characterized by a temperate climate with moderate temperature, rainfall, and relative humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the low prevalences of B. bigemina at T2BF and of A. marginale at T0BF and T2BF could be attributed to the low infestation of cattle by R. decoloratus (Walker, 2003), one of their vector ticks. The occurrence of this species is known to be favoured by low rainfall (Sungirai et al, 2018) such as the beginning of rainy season at T1BN. Tick-borne pathogens identifications in cattle blood were confirmed by their presence in tick DNA samples.…”
Section: Discussionmentioning
confidence: 99%
“…(B.) microplus is a species of Indo-Asian origin 18 that is widely distributed in tropical and subtropical regions between 32°N and 35°S latitude, in areas with an average annual rainfall of 750 to 1000 mm, a temperature range between 12°C and 24°C and altitudes from 250 to 1600 meters above sea level; 9,19 however, as a result of climate change, R. (B.)…”
Section: Rhipicephalus (Boophilus) Microplusmentioning
confidence: 99%